Uso de biofiltração na remoção do sulfeto de hidrogênio presente no biogás - Aita, Bruno Carlesso (2014)
Biogas is an end product of anaerobic degradation of organic substances and has limited use in power generation mainly due to the presence of hydrogen sulfide (H2S). Currently, most of the techniques employed in the removal of H2S from biogas have a chemical base, with high material costs and generating secondary pollutants. The biological processes for the removal of H2S have become an effective and economical alternative to traditional gas treatment systems based on physicochemical techniques. Therefore, the aim of this work was to investigate the performance of a bench scale biofilter for the removal of H2S present in synthetic biogas. In addition, the concentrations of CO2 and CH4 in the effluent biogas were evaluated. The inoculum used in the experiment was composed of Acidithiobacillus thiooxidans fixed on a packing of wood chips. The synthetic biogas was supplied to the system with a composition of 60% CH4, 39 % CO2 and 1 % H2S. The determination of the concentration of hydrogen sulfide was performed by voltammetry and the concentrations of CH4 and CO2 by gas chromatography. The biofilter operated continuously for 37 days with an average removal efficiency of H2S of 75 ± 13 % and maximum of 97%. The elimination capacity of the system reached an average of 130 ± 23 g.m-3.h-1 and a maximum of 169 g.m3.h-1. The biofiltration system showed an average reduction of only 6 % in the CH4 content of the biogas. Thus, besides efficiently being used for the removal of H2S, the system was able to maintain the biogas energy value.